Ankyrin-3 as a molecular marker of early-life stress and vulnerability to psychiatric disorders - Luoni, Alessia; Witt, Stephanie; Gass, Peter; Rietschel, Marcella; Deuschle, Michael (Translational Psychiatry, 2016)
Exposure to early-life stress (ELS) may heighten the risk for psychopathology at adulthood. Here, in order to identify common genes that may keep the memory of ELS through changes in their methylation status, we intersected methylome analyses performed in different tissues and time points in rats, non-human primates and humans, all characterized by ELS. We identified Ankyrin-3 (Ank3), a scaffolding protein with a strong genetic association for psychiatric disorders, as a gene persistently affected by stress exposure. In rats, Ank3 methylation and mRNA changes displayed a specific temporal profile during the postnatal development. Moreover, exposure to prenatal stress altered the interaction of ankyrin-G, the protein encoded by Ank3 enriched in the post-synaptic compartment, with PSD95. Notably, to model in humans a gene by early stress interplay on brain phenotypes during cognitive performance, we demonstrated an interaction between functional variation in Ank3 gene and obstetric complications on working memory in healthy adult subjects. Our data suggest that alterations of Ank3 expression and function may contribute to the effects of ELS on the development of psychiatric disorders.
Gesehen am 03.06.2019